2006
DOI: 10.2337/dc05-2141
|View full text |Cite
|
Sign up to set email alerts
|

A Risk Score for Predicting Incident Diabetes in the Thai Population

Abstract: OBJECTIVE -The objective of this study was to develop and evaluate a risk score to predict people at high risk of diabetes in Thailand.RESEARCH DESIGN AND METHODS -A Thai cohort of 2,677 individuals, aged 35-55 years, without diabetes at baseline, was resurveyed after 12 years. Logistic regression models were used to identify baseline risk factors that predicted the incidence of diabetes; a simple model that included only those risk factors as significant (P Ͻ 0.05) when adjusted for each other was developed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
218
6
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(260 citation statements)
references
References 20 publications
(10 reference statements)
15
218
6
4
Order By: Relevance
“…These studies have shown that although the prevalence continues to increase with age, the incidence of diabetes plateaus in elderly individuals. Our study is consistent with several other observational studies in finding alcohol intake to be protective (25,26) and increased triglycerides to be a putative risk factor for NOD (27,28). Somewhat counterintuitively, raised total cholesterol appeared to be protective in these analyses, although this finding too has been reported in other trials (8 -10).…”
Section: Risk Scoressupporting
confidence: 92%
“…These studies have shown that although the prevalence continues to increase with age, the incidence of diabetes plateaus in elderly individuals. Our study is consistent with several other observational studies in finding alcohol intake to be protective (25,26) and increased triglycerides to be a putative risk factor for NOD (27,28). Somewhat counterintuitively, raised total cholesterol appeared to be protective in these analyses, although this finding too has been reported in other trials (8 -10).…”
Section: Risk Scoressupporting
confidence: 92%
“…Comparisons with other studies Previous studies of screening have focused on risk factor questionnaires, glucose-related measures and risk factor combinations of demographics, anthropometrics and laboratory measurements. Questionnaires are inexpensive and some have been reported to provide AROC for diabetes of~0.80 [21], comparable to that of RPG in the present study, with most providing AROC 0.70-0.75 [22]. In our population, the Diabetes Risk Calculator [23] provided AROC 0.70 for diabetes and 0.67 for prediabetes 110 .…”
Section: Discussionsupporting
confidence: 53%
“…Combining information on FPG or impaired fasting glucose with a simple diabetes risk score has been reported to increase predictive ability [7,8,[12][13][14][15][16][17]. A study reported that screening models using the combination of HbA 1c , BMI and FPG accurately identified individuals at risk of future clinically diagnosed diabetes [22], although the factors that remained significant were different from those found in the present study.…”
Section: Discussioncontrasting
confidence: 51%
“…Various rules have been developed to predict the incidence of diabetes in different ethnic groups [2][3][4][5]. Routine clinical markers available without laboratory testing have been shown to be predictive of the development of diabetes [6][7][8][9][10][11][12][13][14][15][16][17][18] and adding biochemical measures, in particular fasting plasma glucose (FPG), improves predictive accuracy [7,8,[12][13][14][15][16][17]. On the other hand, adding complex data such as the results of oral glucose tolerance tests and measurements of insulin levels and inflammatory markers into a simple clinical model only minimally improves risk prediction while increasing cost and inconvenience [10,19].…”
Section: Introductionmentioning
confidence: 99%